Odpowiedzi

2010-01-26T11:37:01+01:00
X+y=0
3x+2y=-2

x = 0 - y
3(0 - y) + 2y = -2

x = 0 - y
-3y + 2y = -2

x = 0 - y
-y = -2 /(-1)

x = 0 - y
y = 2

x = -2
y = 2
2010-01-26T11:38:42+01:00
X+y=0
3x+2y=-2

x=-y
3(-y)+2y=-2

x=-y
-3y+2y=-2

x=-y
-y=-2/(-1)

x=-y
y=2

x=-2
y=2
Najlepsza Odpowiedź!
2010-01-26T11:43:29+01:00
1. x+y=0
3x+2y=-2

2. x = 0 - y
3(0 - y) + 2y = -2

3. x = 0 - y
-3y + 2y = -2

4. x = 0 - y
-y = -2 /(-1)

5. x = 0 - y
y = 2

x = -2
y = 2

Spr.
x+y=0
-2+2=0

3x+2y= -2
3*(-2)+2*2=-2
-6+4=(-2)